2018
DOI: 10.7717/peerj.6032
|View full text |Cite
|
Sign up to set email alerts
|

Complete chloroplast genome sequences of Dioscorea: Characterization, genomic resources, and phylogenetic analyses

Abstract: Dioscorea L., the largest genus of the family Dioscoreaceae with over 600 species, is not only an important food but also a medicinal plant. The identification and classification of Dioscorea L. is a rather difficult task. In this study, we sequenced five Dioscorea chloroplast genomes, and analyzed with four other chloroplast genomes of Dioscorea species from GenBank. The Dioscorea chloroplast genomes displayed the typical quadripartite structure of angiosperms, which consisted of a pair of inverted repeats se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 50 publications
17
30
1
Order By: Relevance
“…As shown in the previous studies, our comparison also confirmed that the IR region was more conserved than the LSC and SSC regions within these species ( Fig. 3; Zhao et al, 2018;Ma et al, 2018).…”
Section: Comparative Analysissupporting
confidence: 90%
See 3 more Smart Citations
“…As shown in the previous studies, our comparison also confirmed that the IR region was more conserved than the LSC and SSC regions within these species ( Fig. 3; Zhao et al, 2018;Ma et al, 2018).…”
Section: Comparative Analysissupporting
confidence: 90%
“…The GC contents of the LSC and SSC regions are 31.5% and 31.4%, respectively, whereas that of the IR regions is 42.2%. Similar to other closely related species, the high GC content in IR region is due to the high GC content in four rRNA genes in this region (54.6%; Zhao et al, 2018).…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…The GC content of the Nicotiana species referred to above were similar to those of other Nicotiana species (Sugiyama et al, 2005; Yukawa, Tsudzuki & Sugiura, 2006) i.e. the GC content in the IR is high, which might be a result of the existence of ribosomal RNA (Qian et al, 2013; Cheng et al, 2017; Zhao et al, 2018). The genome organization, gene order and content and of these Nicotiana species were also similar for N. slyvestris and N. tabacum (Sugiyama et al, 2005; Yukawa, Tsudzuki & Sugiura, 2006).…”
Section: Discussionsupporting
confidence: 56%